Annals of Scientific Society for Assembly, Handling and Industrial Robotics 2021 2022
DOI: 10.1007/978-3-030-74032-0_27
|View full text |Cite
|
Sign up to set email alerts
|

Towards Synthetic AI Training Data for Image Classification in Intralogistic Settings

Abstract: Obtaining annotated data for proper training of AI image classifiers remains a challenge for successful deployment in industrial settings. As a promising alternative to handcrafted annotations, synthetic training data generation has grown in popularity. However, in most cases the pipelines used to generate this data are not of universal nature and have to be redesigned for different domain applications. This requires a detailed formulation of the domain through a semantic scene grammar. We aim to present such … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In [ 17 ], this problem is addressed by using synthetic data. The successful use of synthetic training data for the domain of aircraft production and logistic scenarios is addressed by [ 18 , 19 ]. A variety of application scenarios for object identification of industrial components with a high degree of similarity using CNNs are shown in [ 2 , 4 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [ 17 ], this problem is addressed by using synthetic data. The successful use of synthetic training data for the domain of aircraft production and logistic scenarios is addressed by [ 18 , 19 ]. A variety of application scenarios for object identification of industrial components with a high degree of similarity using CNNs are shown in [ 2 , 4 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Related Workmentioning
confidence: 99%
“…However, this requires prior training with a sufficiently large dataset that describes the target domain as completely as possible. To address the problem of unavailable training data, synthetic generation is a possible solution [ 18 , 19 ].…”
Section: Analysis Concept Creation and Data Preparationmentioning
confidence: 99%
“…Focusing on the ability to detect aircraft components in production supplying logistic operations with delivery units, [2,3] provide the capability to enable AI-based visual sensor applications with the help of synthetic training data. Such an approach can be incorporated into the design flow of this paper, however, is limited to components that can be differentiated through means of object detection and a top-view sensor configuration.…”
Section: Related Work and State Of The Artmentioning
confidence: 99%
“…Another essential gap in the l-app study has been the congruency between the information provided by l-apps and the actual experience felt by tourists. Indeed, 1-apps often use professional photographs and videos that are taken in ideal conditions, with perfect lighting and angles [ 22 ]. These images are carefully selected to showcase the best features of a particular attraction or destination.…”
Section: Introductionmentioning
confidence: 99%